Upaya Meningkatkan Kinerja Guru Dalam Proses Pembelajaran di Kelas Melalui Supervisi Akademik Secara Periodik di UPTD SD Negeri 06 Sariak Laweh Tahun Pelajaran 2019/2020 - Abdul Najar (Departement of Mathematics Education, 2022)
The purpose of this principal action research is to improve the competence of teachers at UPTD SD Negeri 06 Sarik Laweh in implementing the learning process through periodic academic supervision at UPTD SD Negeri 06 Sariak Laweh for the 2019/2020 academic year. The type of research used in this research is school action research. The activities in this study consisted of the stages of action planning, action implementation, observation, and reflection. The data collection technique used classroom observation techniques. The observation instrument used was a teacher ability assessment tool (APKG) in the form of a learning administration assessment instrument. Analysis of the data used is a comparative descriptive analysis technique. The quantitative data obtained are described in the form of words or explanations. Furthermore, data comparisons were carried out to ensure whether there was an increase in the teacher's ability in the assessment of learning administration. The results showed that academic supervision can improve the ability of teachers in implementing the learning process and assessment in learning at UPTD SD Negeri 06 Sarik Laweh.